A review on polyphosphate coacervates—structural properties and bioapplications - Franco, Douglas F. [UNESP]; De Oliveira Barud, Hélida G. [UNESP]; Barud, Hernane S.; Oliveira Júnior, Osmir B. [UNESP]; Meneguin, Andréia B.; de Oliveira, Luiz Fernando C.; Silva, Maurício A. P.; Ribeiro, Sidney J. L. [UNESP]; Nalin, Marcelo [UNESP] (My University, 2020)
The coacervation process of Graham’s Salt Na(PO3)n enabled the preparation of polyphosphate coacervates (CPPs) by adding different metallic ions (Mn+), and/or low-molecular-weight solvents at a specific solution, which resulted in a phase separation. The more viscous phase is termed as CPP and the less viscous one is the supernatant. CPPs have been extensively studied in recent years as a glass precursor at room temperature. Preparation at room temperature allows the preservation of the physicochemical properties of a wide range of active principles that may be used in controlled drug-delivery systems. Despite the present limitations of CPPs in terms of high hygroscopicity, this vulnerability to water is considered one of the great advantages of this material regarding applications in the controlled release of drugs and tissue engineering. Thus, in the presence of water, CPPs will dissolve in calcium and phosphate ions, which are the major inorganic constituents of bone and hydroxyapatite (HAP). It is believed that, in contact with body fluids, CPPs will degrade and, as this process occurs, they will be replaced by HAP. Therefore, CPPs configure a potential biomaterial that offers excellent properties with a wide range of biomedical applications that will be discussed and reviewed in this paper, including the structural properties and the recent improvements of materials based on CPPs and related devices. [Figure not available: see fulltext.]
Keywords: Bioglasses; Biomedical applications; Drug-delivery systems; Graham’s salt; Polyphosphate coacervates